Corporate governance : a framework for implementation - Iskander, Magdi R.; Chamlou, Nadereh (Washington, D.C. : World Bank, 2000)
This report examines the establishment of trust and the encouragement of enterprise and focuses on the principles of corporate governance which aim to align the interests of individuals and corporations.
with a foreword by Sir Adrian Cadbury.
Includes bibliographical references (p. 203-210).
oif 25/03/15
Loan
Keywords: Corporate governance